Frontiers of intelligent control and information processing - Liu, Derong 1963-; Alippi, Cesare; Zhao, Dongbin; Huaguang, Zhang (World Scientific, 2014)
This review volume encapsulates the state-of-art pioneering works in the development of intelligent control systems. Proposition and evocations of each solution is backed up with evidences from applications, could be used as references for the consideration of decision support and communication components required for today intelligent control systems